Combustion Characteristics of a Semi-Adiabatic Diesel Engine with Plastic Oil with Supercharging - Machiraju, Aditya Seshu; Krishna, M. V. S. Murali; Ushasri, P. (Techniques and Innovation in Engineering Research Vol. 1, 2022)
Waste plastic is non-biodegradable. It causes health hazards to human beings and cattle. Scientists have found that it is carcinogenic in nature. If plastic is converted to oil, which can be used in Internal Combustion Engines. In the context of fast depletion of fossil fuels, ever increase of pollution levels with fossil fuels and increase of economic burden towards import of crude petroleum, which could have spent another important sectors like health, poverty, literacy, agriculture etc., the search for alternative fuels has become pertinent. Alcohols and vegetable oils are important substitutes for diesel fuel, as they are renewable in nature. Alcohols have high volatility, but low calorific value and cetane ( a measure of combustion quality in diesel engine) number. On the other hand, vegetable oils have comparable calorific value, and cetane number. But they have high viscosity and low volatility. Plastic oil can be manufactured from waste debris by the process known as pyrolysis, is a good substitute for diesel fuel, as its properties are comparable with diesel fuels. However, plastic oil has high viscosity. In order to reduce viscosity and improve cetane number diethyl ether (DEE) of optimum quantity (15%) was added to the plastic oil. These viscous fuels can be effectively burnt in low heat rejection engine or semi adiabatic diesel engine (SADE). The concept of SADE is to minimize the heat loss to the coolant thus creating hot combustion chamber suitable for burning high viscous fuels. The SADE consisted of air gap insulated engine. It is necessary to find out or to evaluate combustion characteristics of the test fuels, if the design of combustion chamber was changed from conventional combustion chamber to insulated combustion chamber. The aim of this report was to determine combustion characteristics of peak pressure (PP), time of occurrence of peak pressure (TOPP) and maximum rate of pressure rise (MRPR) at full load operation of the engine with both versions of the engine such as conventional engine (CE) and SADE with and without supercharging with varied injection timing. Supercharging is defined as additional supply of (oxygen) air at high pressure at inlet manifold of the engine to improve the performance of the engine The piezo electric transducer was connected to the top portion of the cylinder head, while TDC (top dead centre) encoder was connected to the extended portion of the extended shaft of the dynamometer. The console was connected to the transducer and TDC encoder. The console converts pressure signal from transducer and magnetic signal from TDC encoder to electric signal fed to the computer. The computer reads the data of combustion parameters at full load operation. The injection timing was varied with an electronic sensor. Combustion characteristics improved with SADE at full load operation with advanced injection timing.